Strategi Pemasaran Offline Efektif Untuk Meningkatkan Jangkauan dan Penjualan di dalam dan Luar Kota - Neli Purwanti; Abdul Hamid (Yayasan Daarul Huda Kruengmane, 2025)
This community service program aims to enhance the capacity of micro and small business actors in Bojongloa Village, Buahdua District, Sumedang Regency, in implementing effective offline marketing strategies to expand market reach and increase sales both within and outside the city. The main problems faced by partners include limited knowledge of structured conventional marketing strategies, low product packaging attractiveness, and underutilized local and regional distribution networks. The methods used include socialization, training, mentoring, and evaluation of offline marketing strategy implementation, covering packaging improvement, simple branding, direct promotion, utilization of local events, and strengthening distribution networks. The results indicate increased partner understanding of offline marketing, improved product appearance, expanded marketing networks, and gradual sales growth. This program is expected to serve as a sustainable model for village-based UMKM empowerment through offline marketing strategies.